Pengaruh Literasi Digital, Social Influence, dan Persepsi Keamanan Terhadap Transaksi Penggunaan QRIS Masyarakat Kecamatan Johan Pahlawan - Saputri Sitompul, Ningsi; Mandaira , Fitria; Lishanti, Tio Devi (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to analyze the influence of digital literacy, social influence, and security perception on the actual transactions of the community in Johan Pahlawan District as QRIS users. The research employed a quantitative approach with the Partial Least Square (PLS) analysis technique. A total of 100 respondents were selected using the Slovin formula. Data were collected through questionnaires with a Likert scale. The results show that digital literacy has a positive and significant effect on actual transactions, as does security perception which also has a positive and significant effect. However, social influence does not have a significant effect on actual transactions. These findings indicate that the decision to use QRIS is more strongly influenced by digital literacy and security perception rather than social encouragement. This study contributes theoretically to the literature on digital financial technology adoption and provides practical implications for the government and financial service providers in improving digital literacy and transaction security to expand QRIS adoption in the region.